Determinants of Investment in District/City Province of Central Java - Putratsalaatsa, Muhammad Bagus (Universitas Negeri Semarang, 2020)
The purpose of this study was to analyze the determinants of investment in Central Java in 2014-2018, classifying each district / city in Central Java based on investment realization, and the factors influencing investment in Central Java. The variables used in this study are Investment, Labor, HDI, Regional Minimum Wage and CPI. The data used in this study are cross section and time series data from 2014-2018 sourced from DPMPTSP and BPS. The method used in this study is Klassen Typology and Multinomial Logistic Regression. The results showed that: (1) Factors affecting investment, namely the labor variable significantly influence investment. (2) In the classification of developed regions fast-growing factors affecting investment are the labor and regional minimum wages, then for the classification of developed regions depressed factors affecting investment namely the labor and the classification of potential areas of fast developing factors affecting investment namely the labor and HDI. (3) The classification accuracy is 47.4% and the model is suitable but the classification has a low value. The government must implement policies that are pro-investment and strengthen the specialization of each region. Future researchers' recommendations are expected to use more complete predictor variables that are not used in this study which might improve classification accuracy. Tujuan penelitian ini adalah menganalisis determinan investasi di Jawa Tengah tahun 2014-2018, mengelompokkan setiap kabupaten / kota di Jawa Tengah berdasarkan realisasi investasi, dan faktor-faktor yang mempengaruhi investasi di Jawa Tengah. Variabel yang digunakan dalam penelitian ini adalah Investasi, Tenaga Kerja, HDI, Upah Minimum Regional dan IHK. Data yang digunakan dalam penelitian ini adalah data cross section dan time series tahun 2014-2018 yang bersumber dari DPMPTSP dan BPS. Metode yang digunakan dalam penelitian ini adalah Tipologi Klassen dan Regresi Logistik Multinomial. Hasil penelitian menunjukkan bahwa: (1) Faktor yang mempengaruhi investasi yaitu variabel tenaga kerja berpengaruh signifikan terhadap investasi. (2) Dalam klasifikasi daerah maju faktor pertumbuhan cepat mempengaruhi investasi adalah tenaga kerja dan upah minimum daerah, kemudian untuk klasifikasi daerah maju faktor tertekan yang mempengaruhi investasi yaitu tenaga kerja dan klasifikasi daerah potensial faktor cepat berkembang mempengaruhi investasi yaitu tenaga kerja dan HDI. (3) Akurasi klasifikasi adalah 47,4% dan model sudah sesuai tetapi klasifikasi memiliki nilai yang rendah. Pemerintah harus melaksanakan kebijakan yang pro investasi dan memperkuat spesialisasi masing-masing daerah. Rekomendasi peneliti selanjutnya diharapkan dapat menggunakan variabel prediktor yang lebih lengkap yang tidak digunakan dalam penelitian ini yang dapat meningkatkan akurasi klasifikasi.